2009
DOI: 10.1097/aog.0b013e3181922362
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction After Trocar-Guided Transvaginal Mesh Repair of Pelvic Organ Prolapse

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 31 publications
4
30
3
Order By: Relevance
“…Postoperative dyspareunia is the area of sexual dysfunction that has received the greatest attention relating to urogynecological surgery. Again findings from previous studies are conflicting and some studies show an increased risk for dyspareunia after surgery whereas others detected no change [8][9][10][11][12][13][14]. We found that the number of women with dyspareunia decreased postoperatively, even if almost half of the women who answered the question (42/ 98) had some dyspareunia one year after the operation.…”
Section: Tablecontrasting
confidence: 49%
See 2 more Smart Citations
“…Postoperative dyspareunia is the area of sexual dysfunction that has received the greatest attention relating to urogynecological surgery. Again findings from previous studies are conflicting and some studies show an increased risk for dyspareunia after surgery whereas others detected no change [8][9][10][11][12][13][14]. We found that the number of women with dyspareunia decreased postoperatively, even if almost half of the women who answered the question (42/ 98) had some dyspareunia one year after the operation.…”
Section: Tablecontrasting
confidence: 49%
“…The deterioration was mainly attributed to negative effects in the partner related domain whereas the behavioral-emotive and physical domains showed no significant changes. To some extent this concurs with a previous cohort study showing that transvaginal mesh is associated with deteriorating partner related sexual function [8]. Although partner related sexual dysfunction after prolapse surgery is a recurrent finding in studies on pelvic organ prolapse surgery the mechanisms for this finding are poorly understood.…”
Section: Commentcontrasting
confidence: 38%
See 1 more Smart Citation
“…At this point, short-term data (2-year follow-up or less) suggest that its use for anterior compartment defects may provide an advantage over nonmesh augmented repairs [1,2], but at what cost [3,4]?…”
mentioning
confidence: 99%
“…The graft is placed superficial to the fascia in mesh-augmented surgery, whereas it is placed close to the viscus in mesh replacement surgery (A. Rane, personal communication) [17]. Always consider ''His'' and ''Her'' pareunia while planning surgery-male dyspareunia seems invariably associated with stiff graft material exposure, while female dyspareunia seems to be more associated with excessive graft tensioning or with shortening and narrowing of the vaginal canal [18][19][20][21].…”
mentioning
confidence: 99%